Experimental and numerical evaluation of napier grass gasification in an auto-thermal fluidized bed reactor - Khezri, Ramin (2018)
Biomass gasification is a promising renewable energy generation technology as alternative to fossil based fuels for cleaner and sustainable future. At site auto-thermal gasifier built in affordable economic scale can overcome the high costs of grid lining, supplementary resources and the delivery of feedstock as main target for this study. A biomass gasification system with Napier grass as feedstock was investigated with the target of the producer gas to be used in direct combustion for power generation. The study consists of two main parts of experimental evaluations and numerical models. Experiments carried out to study the effect of three different operating parameters namely, temperature, equivalence ratio (ER) and static bed height (SBH) on the gasification of Napier grass in an auto-thermal bubbling fluidized bed gasifier. The results showed that the temperature has the most significant effect on the production of syngas as well as the composition of combustible species. The highest yield of syngas, with highest compositions of hydrogen and carbon monoxide and lowest yield of residues (i.e. biochar, tar and ash) were achieved at maximum temperature of 824°C. ER on the other hand has more complex effects on responses. The increase in ER up to 0.33 favored the yields of syngas, H2 and CO however the inverse effect was observed for ER above 0.33. SBH was found an important factor to effect on the production of H2 and CO and the maximum yields of each obtained at temperature of 824°C, ER of 0.33 and SBH of 0.105m. Common challenges encountered in performing the experiments were related to the complexity and instability of the process and the difficulties to maintain the temperature at a constant level due to the auto-thermal characteristics. Difficulties are expected to be diminished once achieved a steady-state operating condition through process improvement and optimization to which the process become adaptable to any imposed variations such as different feedstock types.An integrated numerical simulation were developed to study over hydrodynamics and thermodynamics of the gasification process. Hydrodynamics of solid particles fluidization were modelled to study on the effect of superficial velocity, viscous and drag models on the expansion of fluidizing bed, formation and distribution of bubbles inside the gasifier. The effect of air distributor plate with different pore diameters was modelled individually to determine the initial condition of the fluid as entered the gasifier. The results showed that the turbulent model of RNG K-Ɛ describes the actual process more accurately than other fluid regimes. Laminar and turbulent models although resulted in similar bed expansion level, the turbulent model showed higher distribution of solid particles and their related interactions as the result. Thermodynamic studies were conducted to simulate the heat distribution and to determine the temperature profile of the reactor at any time step of the operation. The temperature values at steady operation were verified by experimental records. The conduction heat transfer from gasifier media into the center of a single particles with different diameters were studied individually to calculate the particle degradation period. It was found from the results that fully degradation of a particle to solid biochar as entered the gasifier at constant temperature takes place after 0.66, 1.1 and 1.55 seconds for particles with 300,500 and 700 μm diameters respectively. The effect of particle size and initial reactor temperature on heat distribution were evaluated as well. Using the model eases the monitoring of system behavior while functions under various operating conditions. The findings from empirical optimization while integrated with numerical models provides an in-depth understanding over the gasification process and facilitates the scale-up determinations so that the technology in the future can be utilized in larger scales to provide power from biomass particularly in form of electricity in rural area.